Pembuatan Business Plan Bidang Usaha Furniture di PT. Kirmizhi Foam Indonesia - Laurentius Pasca; Felecia Felecia (Jurnal Titra, 2020)
PT. Kirmizhi Foam Indonesia is a manufacturing company moving in the foam and cushion production department. Currently, PT. Kirmizhi Foam Indonesia is spreading their wings to the furniture industry, due to the very high demand in the furniture market. This research is done based on the steps on creating business plan.  The steps of making business plan are: executive summary, enterprise description, product or service description, industry analysis, competition analysis, SWOT analysis, marketing sub-plan, operation sub-plan, human resources sub-plan, financial sub-plan, risk analysis, dan milestone schedule. The result of this research is that the furniture business plan is worthy to be run by PT. Kirmizhi Foam Indonesia by looking at the target market intended, furniture market analysis, competitors analysis, SWOT analysis, market planning, operational consideration, as well as the financial result which has 11% IRR.